Analisis Kompetensi Teknis Tour guide Pada Kesiapan Praktik Guiding Siswa SMK Harapan Bersama Kota Tegal - Puput Dewi Anggraeni (LPPM Universitas Bina Sarana Informatika, 2025)
The technical competence of tour guides is very important for students majoring in Tourism Service Business at Harapan Bersama vocational high school in Tegal City, because it is the main foundation for conducting guiding practices for students who want to become tour guides. These competencies include knowledge, skills, and attitudes. In addition, students are also required to learn to memorize, explain general and important information that is around them, including general knowledge in a comprehensive manner. The technical competence of tour guides must be possessed by students so that their readiness in guiding becomes trained and confident in explaining knowledge of tourist attractions and their surroundings. Therefore, the analysis of the technical competence of tour guides needs to be carried out and followed up further, so that students have a better mastery of the material studied and are ready to carry out guiding practices. This research is a quantitative research. The purpose of this study is to analyze the technical competence of tour guides on the readiness of guiding practices of Harapan Bersama vocational high school students in Tegal City. The sample in this study amounted to 19 respondents. The sampling technique in this study used simple random sampling. This study used descriptive analysis. The results of this study are indicators that can be described: The knowledge indicator shows an average value of 61.59% which means that knowledge is very important for a tour guide, because it is the main provision and foundation for students in providing explanations about history, culture, tourist destinations and facts in a city that will be visited so that the information provided is clear and guests feel satisfied with the explanation given by the tour guide. The skill indicator shows an average value of 65.8% which means that trained skills are needed by a tour guide in explaining or conveying stories well to guests, managing time and handling emergency situations during the tour. The attitude indicator shows an average value of 77.86% which means that attitudes in tour guide competencies are very important and must be possessed by a tour guide, because a tour guide must be able to serve guests well, so that guests feel satisfied with the services provided during the tour. The readiness indicator shows an average value of 73.7% which means that the readiness of practical guiding of Harapan Bersama vocational high school students majoring in Tourism Service Business must be supported by the existence of technical tour guide competencies including knowledge, skills, and attitudes.